2018
DOI: 10.1186/s13731-018-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

Ambidextrous leadership, ambidextrous employee, and the interaction between ambidextrous leadership and employee innovative performance

Abstract: Leader opening and closing behaviors are assumed to foster high levels of employee exploration and exploitation behaviors, hence motivating employee innovative performance. Applying the ambidexterity theory of leadership for innovation, results revealed that leader opening and closing behaviors positively predicted employee exploration and exploitation behaviors, respectively, above and beyond the control variables. Moreover, results showed that employee innovative performance was significantly predicted by le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(173 citation statements)
references
References 46 publications
7
129
2
8
Order By: Relevance
“…They conclude that daily innovative performance will be highest when both transactional and transformational behaviors are high. These results are in line with the research by Alghamdi (2018), conducted in Saudi Arabia.…”
Section: Ambidextrous Leadershipsupporting
confidence: 92%
See 1 more Smart Citation
“…They conclude that daily innovative performance will be highest when both transactional and transformational behaviors are high. These results are in line with the research by Alghamdi (2018), conducted in Saudi Arabia.…”
Section: Ambidextrous Leadershipsupporting
confidence: 92%
“…Previous studies on ambidextirity are mostly in the organizational context (Fourne, Sebastian, Jansen, Justin, Rosenbusch, 2016, Uotila, 2012, Kim, Bansal & Haugh, 2019, radical innovation (Blank & Naveh 2013), organizational learning (Levitt, Barbara, 2011), research and development (Swift, 2016), management systems (Burton, O'Reilly & Bidwell 2012) , and accountability (Verwaeren, Buyens & Baeten 2016) with unfortunately very limited studies of ambidextirity on leadership. The existing literature on ambidextrous leadership categorizes ambidextrous leadership into two categories: opening (exploration) and closing (exploitation) (Zacher & Wilden, 2014;Alghamdi, 2018), which we herein after refer to as tranformational leadership and transactional leadership in Indonesia. Leaders as the decision makers and are the keys to gaining competitive advantages (Solís-Molina, Hernández-Espallardo & Rodríguez-Orejuela, 2018), superior firm performance (Arzubiaga et.…”
Section: Introductionmentioning
confidence: 99%
“…Managers must be responsible for coordinating HRM towards exploration and/or exploitation activities. Jansen et al [32] and Alghamdi [33] have reported that ambidextrous HRM helps to generate greater group cohesion and a more proactive attitude towards innovation.…”
Section: Ambidextrous Organizational Approachmentioning
confidence: 99%
“…Работы многих авторов фокусируются на влиянии неопределенности внешней среды на деятельность организации [6,7]. Учитывая, что внешняя среда изменяется достаточно быстро, долгосрочное развитие организации зависит от того, насколько она может эффективно использовать текущие и исследовать будущие возможности [8]. В разгар пандемии короновируса COVID-19 большинство российских предприятий перенесли шок от действий правительства по жесткому купированию ситуации.…”
Section: Introductionunclassified
“…Поэтому считается, что структурная неопределенность влияет на внутреннюю структуру организации, на ее реакцию на изменение внешних условий, а контекстная неопределенность -на состав и квалификацию персонала организации [8].…”
Section: Introductionunclassified